2015
DOI: 10.1007/s10439-015-1397-1
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-Based Electrical Plethysmography Approach to Bladder Volume Measurement

Abstract: Neuromodulation approaches to treating lower urinary tract dysfunction could be substantially improved by a sensor able to detect when the bladder is full. A number of approaches to this problem have been proposed, but none has been found entirely satisfactory. Electrical plethysmography approaches attempt to relate the electrical impedance of the bladder to its volume, but have previously focused only on the amplitudes of the measured signals. We investigated whether the phase relationships between sinusoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Bladder volume monitoring using electrical impedance (EI) techniques has been studied in simulation , with simplified tank-based measurements (He et al, 2012;, on animals (Denniston and Baker, 1975;Zariffa et al, 2016), and on humans (Kim et al, 1998;Leonhardt et al, 2011;Liao and Jaw, 2011;Zariffa et al, 2016, Shin, et al, 2017. Human studies have shown strong correlation of bladder volume with the processed EI data (Leonhardt et al, 2011;Li et al, 2016), highlighting the feasibility of EI to continuously monitor bladder volume in clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder volume monitoring using electrical impedance (EI) techniques has been studied in simulation , with simplified tank-based measurements (He et al, 2012;, on animals (Denniston and Baker, 1975;Zariffa et al, 2016), and on humans (Kim et al, 1998;Leonhardt et al, 2011;Liao and Jaw, 2011;Zariffa et al, 2016, Shin, et al, 2017. Human studies have shown strong correlation of bladder volume with the processed EI data (Leonhardt et al, 2011;Li et al, 2016), highlighting the feasibility of EI to continuously monitor bladder volume in clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence (UI) is the involuntarily discharge of urine 1 , and it affects over 200 million people worldwide 2 . The condition may develop in an individual due to advancing age 3 , 4 , urinary tract infections 3 , diabetes 3 , 5 , or due to a neurological disease such as stroke, spinal cord injury, or multiple sclerosis 3 , 6 . Urinary Incontinence can be associated with urinary tract infections, urinary reflux and even renal damage and failure 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 and Zariffa et al . 6 . The results from these studies have shown a strong correlation between the processed electrical impedance data and the bladder volume.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence affects over 200 million people throughout the world [1]. In particular the condition affects children and adolescents with intellectual disabilities [2], the elderly [3], [4] and those with neurological conditions [5]. Urinary incontinence can severely impact the quality of life of these individuals [6], [7].…”
Section: Introductionmentioning
confidence: 99%